2018
DOI: 10.1016/j.cdtm.2018.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Tumor‐associated macrophages (TAMs) as biomarkers for gastric cancer: A review

Abstract: Gastric adenocarcinoma is one of the most common types of cancer worldwide, with an incidence of a million new cases annually. In addition to having a high mortality rate due to often delayed detection and its poor response to cancer therapy, it also spreads aggressively. Inflammation has been shown to play a role in carcinogenesis. Consequently, macrophages are important in phagocytosis, antigen presenting and producing cytokines and growth factors. As a response to microenvironmental signals, they may polari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
58
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(63 citation statements)
references
References 48 publications
1
58
0
Order By: Relevance
“…According to some reports, they can be positive and, according to others, negative prognostic factors. Prominent macrophage infiltrates are considered to be an adverse prognostic factor in gastric or breast cancer [22,23], whereas controversial results were shown for bladder, lung and thyroid cancer [24][25][26].…”
Section: Discussion/conclusionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to some reports, they can be positive and, according to others, negative prognostic factors. Prominent macrophage infiltrates are considered to be an adverse prognostic factor in gastric or breast cancer [22,23], whereas controversial results were shown for bladder, lung and thyroid cancer [24][25][26].…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…Several studies have evaluated the prognostic or predictive significance of TAMs in different neoplasms with ambiguous results. Intense infiltrates of TAMs were linked to unfavourable prognosis in gastric or breast cancer [22,23], whereas controversial results were shown for bladder, lung, and thyroid cancer [24][25][26]. Results obtained for oropharyngeal cancer are also contradictory especially in the context of HR-HPV status and macrophage phenotype.…”
Section: Introductionmentioning
confidence: 99%
“…They modulate tumorigenesis and adjust the response to therapy. Several studies have reported that TAMs are related to poor prognosis in different tumors as hepatocellular carcinoma, gastric cancer, and lung cancer [15]. Several markers are used to label macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…Wnt5a might also be secreted by tumor-associated macrophages (TAMs), which are observed in GC and correlate with poor prognosis (Räihä and Puolakkainen, 2018). Macrophages secrete Wnt5a in response to LPS treatment and H. pylori infection (Zhao et al, 2013).…”
Section: Wnt5a Expression In Gastric Cancermentioning
confidence: 99%